PERTUMBUHAN TANAMAN PADI PADA BAHAN GAMBUT YANG DIPERLAKUKAN DENGAN HERBISIDA PARAQUAT, KAPUR DAN PUPUK NPK = THE GROWTH OF RICE ON PEAT SOIL TREATED WITH PARAQUAT HERBICIDE, LIME AND NPK-FERTILIZERS - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
This study was conducted to investigate the growth and yield of rice (IR-64 variety) on peat soil added with paraquat herbicide. Two kinds of peat soils, i.e. fibric and saphric, were obtained, from The Province of Central Kalimantan. The soils were treated with lime and NPKÂ¬fertilizers. Physical and chemical characteristics of the peat soil before and after planting were analyzed to know the possible mechanism process occurred due to the soil treatments. The results showed that to obtain optimal rice growth and yield in peat soils need addition of lime and fertilizers. These treatments accelerated vegetative growth and increased yield of the crop. Influence of paraquat herbicide on rice crop was depend on the kind of peat soil. Addition of paraquat inhibited vegetative growth and decrease the number of shoot and rice yield. Even, after around 4 weeks the crops grown in saphric soil added with paraquat died. Soil treatments i.e. fertilizer and/or lime addition, decreased the negative effects of paraÂ¬quat. Due to the needs of herbicide application in peat soil to obtain maximal yield, the soil must be treated with appropriate soil treatments. This study also discussed the physical and chemical changing of soil characteristics which may responsible to the failure of rice growth in the peat soil treated with paraquat herbicide. Keywords : Rice , Peat soil, Paraquat.